Interpreting of Live Press Conferences into Lithuanian Sign Language Under Extreme Conditions of the COVID-19 Pandemic - Stankevič, Natalija; Mankauskienė, Dalia (Vertimo studijos, 2021)
The article presents a study of the work of Lithuanian Sign Language (LSL) interpreters in the spring of 2020, when live press conferences on the COVID-19 pandemic were interpreted. At the onset of the pandemic, LSL interpreters, like many other national sign language interpreters, were faced with a new form of live interpreting − interpreting under extreme conditions. Over the years the broadcast news interpreting has become routine for LSL interpreters and can be considered as interpreting under normal conditions. During the pandemic, however, LSL interpreters suddenly found themselves having to interpret live press conferences of politicians and experts on the evolving situation of COVID-19, a major challenge. Until then, none of them had ever had to interpret under similar conditions in an environment of tension and uncertainty, and without special training of how to interpret in an emergency. The study was based on the methodology of R. L McKee (2014) for studying the sign language interpreters’ work under extreme conditions during the natural disasters in Australia and New Zealand and distinguished environmental, linguistic, paralinguistic and interpersonal factors, and on in-depth interview with all 9 LGK interpreters who interpreted during live press conferences on the COVID-19 pandemic. It examines how these four factors influenced the work of LSL interpreters.